Structural elucidation, bio-inspired synthesis, and biological activities of cyclic diarylpropanes from Horsfieldia kingii. Issue 40 (2nd October 2020) - Zhan, Rui; Li, Dashan; Liu, Yuan-Lie; Xie, Xiao-Yan; Chen, Lei; Shao, Li-Dong; Wang, Wen-Jing; Chen, Ye-Gao
Abstract: Bioactivity-guided phytochemical investigation on 70% aqueous acetone extracts of the twigs and leaves of Horsfieldia kingii led to the isolation of two novel cyclic diarylpropanes (1 and 2 ) bearing a 2, 3-dihydro-1 H -indene core, one new diarylpropane (3 ), six known diarylpropanes (4 –9 ), one flavanol (10 ), and seven lignans (11 –17 ). Their structures were determined by extensive spectroscopic analysis, electronic circular dichroism calculations, and X-ray diffraction crystallography. Moreover, a biomimetic synthesis of 1 and 2 were accomplished in four steps. The in vitro nitric oxide production inhibition tests of these compounds revealed that compounds (±)-2, (+)-2, (−)-2, and 10 were potential with IC50 values lower than 10 μ M. Compound 2 could inhibit iNOS expression in LPS-induced RAW264.7 cells at a series of non-cytotoxic concentrations (<20 μ M). Furthermore, the bioassay results also suggested the primary SARs of 1-phenyl-2, 3-dihydro-1 H -indene based scaffold. Graphical abstract: Image 1 Highlights: 17 compounds were isolated from Horsfieldia Kingii. Horsfielenides C (1 ) and D (2 ) were novel cyclic diarylpropanes bearing a 2, 3-dihydro-1 H -indene core. A biomimetic synthesis of 1 and 2 were accomplished in four steps. Horsfielenide D (2 ) was the most potential compound to inhibit NO production with IC50 value of 4.40 ± 0.69 μ M.